Reversible Cerebral Lession and Irreversible Cerebral Necrosis After Cardiorespiratory Arrest: A Case Report - Tong, Dao-Ming; Zhou, Ye-Ting; Chen, Xiao-Dong (Journal of Neurological Research And Therapy, 2015)
This case contrasts reversible cerebral lesions with areas of irreversible necrosis following cardiorespiratory arrest. The authors discuss imaging evolution, mechanisms of hypoxic–ischemic injury, and implications for prognostication and rehabilitation.
Keywords: Cerebral Necrosis; Cardiorespiratory Arrest; Cerebral Lesions; Hypoxic-Ischemic Injury; Rehabilitation